If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10x+7=-3x+7
We move all terms to the left:
10x+7-(-3x+7)=0
We get rid of parentheses
10x+3x-7+7=0
We add all the numbers together, and all the variables
13x=0
x=0/13
x=0
| 8(3x–7)=-6(x+7)+4 | | 7x-4-x=25 | | 1/2(2-2x)+2x=13 | | 3x+3x+20+110=180 | | 100/x=5.2 | | 5(x-3)=35. | | r/2+5=6.9 | | 4x-2(x-5)=-8+5x+5 | | 7+8x=6x+17 | | 2/3(5x-6)=-2 | | 45-7x=78 | | 6x-14-5x=8 | | h/2-4.87=-3.87 | | 13y+39=1 | | 4=5x+7=13 | | ∣x−1∣+5=2 | | 5+5(n-7)=-40+5n | | 9.2c+14.82=7.3c | | 2/7=-2/3v-1/2 | | 2x+60=2x+30 | | 1/2x+1/2x(x-15)+100(x-25)=540 | | 4x+3=-5x+21* | | -5(4x-3)=2-(16x-11) | | C=45m+25 | | b/2-(-0.75)=1.75 | | p+1/2=3p7/5 | | 10(x+4)-3=14x+1. | | 5m+6=-4m-21 | | −2∣5x−1∣−3=−11 | | -1.4k+15.99+17.98=-17.23-4.6k | | 17=2g-3 | | 6x-12=1x+8 |